Diversity of Giant Viruses Infecting Vermamoeba vermiformis - Geballa-Koukoulas, Khalil; La Scola, Bernard; Blanc, Guillaume; Andreani, Julien (Frontiers in Microbiology, 2022)
The discovery of Acanthamoeba polyphaga mimivirus in 2003 using the free-living amoeba Acanthamoeba polyphaga caused a paradigm shift in the virology field. Twelve years later, using another amoeba as a host, i.e., Vermamoeba vermiformis, novel isolates of giant viruses have been discovered. This amoeba–virus relationship led scientists to study the evolution of giant viruses and explore the origins of eukaryotes. The purpose of this article is to review all the giant viruses that have been isolated from Vermamoeba vermiformis, compare their genomic features, and report the influence of these viruses on the cell cycle of their amoebal host. To date, viruses putatively belonging to eight different viral taxa have been described: 7 are lytic and 1 is non-lytic. The comparison of giant viruses infecting Vermamoeba vermiformis has suggested three homogenous groups according to their size, the replication time inside the host cell, and the number of encoding tRNAs. This approach is an attempt at determining the evolutionary origins and trajectories of the virus; therefore, more giant viruses infecting Vermamoeba must be discovered and studied to create a comprehensive knowledge on these intriguing biological entities.